El tiempo que determina la ley y el perjuicio patrimonial en la configuración de la unión de hecho. - Rojas Fajardo, Linda Pilar (2013)
This research addresses the problem that happens in a Union of Fact, which has recognized the stable and monogamous, between a man and a woman, marriage free in order to live together, procreate and help each other, gives rise to a real company., but for some reason this union, the association of both parties is dissolved in time not established by law, usually the most affected, in this case the woman forfeits his salary real, causing discomfort for the lack of morality and justice of the beneficiary. Likewise, definitions and testimonies gathered citizens and professionals in the field of Law, who gave their opinions about this social phenomenon, as we found many cases in which couples supposedly, have lived a little less than two years, when trying to claim the right of partition of property acquired in his alleged Union of Fact, is faced with the harsh reality when, her partner, has denied invoking the provisions on Article 222. Therefore, in this legal research, we propose the reform of the previous article with the decrease recognition time; this is one years after establishing de facto union, to safeguard the integrity of goods benefits both parties.